Preliminary appointments for geography education and geographical education - Bernardes, Fernando Frederico; Francischett, Mafalda Nesi [UNESP] (Associacao Pro-Ensino Superior em Novo Hamburgo, 2021)
This article reflects on the practice of contemporary School Geography, inspired by two main paradigms: Geography Teaching and Geographic Education. Initially, after the introduction, we point to reflections on the semantic and scientific content referring to the terms teaching and education, Geography Teaching and Geographic Education. Having said that, from the analysis and theoretical findings, we also aim to recognize in the empirical action the relationship between the main research objects. Such verifications become fundamental for the construction, conception, distinction (encounters and mismatches) of these geographical terms, as well as for rethinking and even reconsidering the meaning of geography in schools. At the end of this work, it was possible to demonstrate and substantiate, that in contemporary School Geography, we have as main paradigms the Teaching of Geography and Geographic Education. And the case sample proved to be closer to the Geographic Education aspect, frequently using the following terms: “critical”, “mediation”, “process”, “citizenship” and “subjectivity”. The preliminary contributions were launched and, it is up to the reader / teacher, to make their pedagogical dynamics move with clarity and awareness (planned action), choosing the didactic-pedagogical inspiration with which he / she most believes / identifies.
Aportes preliminares para o ensino de geografia e a educação geográfica
Keywords: Geographic education; Geography teaching; School geography